Mediterranean as method - Chambers, Iain (Itinerari, 2023)
On the map of the Mediterranean everything lies flat, and borders are clearly defined. The topography is rendered evident. All is seemingly captured by the eye, rendered measurable and knowable. This is the basis for the geopolitical chessboard where everything is put on the dissecting table. It seemingly provides a neutral and disinterested (or “scientific”) rendering of reality. But simply by asking who does the mapping, and what does the desire for transparency hide and obscure, we disturb this picture and capture the outline of another Mediterranean. For the power of our maps, where objective measurement confirms our subjective centrality, betrays a cartography of power. Works of art – not as objects restricted to art history and aesthetics, but as a critical apparatus and practice – can be a device capable of disorienting and reorienting our mapping of the modern world, beyond the present structures of power.